Spatio-temporal analysis of trends and patterns in change of male-female literacy in Malda district, W.B. - Siddiqui, Shamsul Haque; Rahaman, Hasibur (National Geographical Journal of India, 2022)
In the present paper, the regional disparity in male-female literacy is highlighted with special focus on spatial and temporal variation at the block level in Malda district of West Bengal. Despite India's achieving universal elementary education, reaching the goal of full literacy is rather difficult owing to the female illiterate population across India's states and districts. According to the 2011 Census of India, the overall literacy rate in the country is 74 per cent, while for male it is 80.9 per cent and 64.6 per cent for female. In the same Census, the respective literacy in Malda districtwas 61.73 per cent in total, while 66.24 per cent for male and 56.96 per cent for female. And within that figure, nearly 40 per cent of males are illiterate, compared with more than 60 per cent of the female. This paper also makes an attempt to map out the comparative analysis of male-female literacy disparity and find out possible reasons.The study is based on secondary data obtained from statistical handbook, UDISE, and Census of India.Sopher method has been used to calculate disparity among male-female literacy and Coefficient of Variation has been used to measure intra-block variation in male-female literacy from 1991 to 2011. After 1991, study founds a swift decline in male-female literacy gap in the study area.It has also found that in between 1991 and 2011, intrablock variationsin male-female literacy reduced by five times in the study region. The study suggests thatthe new strategies and appropriate programmes like universal elementary education should be implemented at its widest sprit in order to realize the goal of full literacy and bridging the gap between male and female literacy. Special provision should be made to bring back 'out-of-school-age' illiterate populationespecially the girls, drop out children and left behind females who were never been in school. To realise the goal of full female literacy, study also suggests the provision of an effective adult-literacy programme with the focus on school left-out female above the age group of thirty.